Structural, optical and magnetic properties of Mn diffusion-doped CdS thin films prepared by vacuum evaporation - Aksu, S.; Bacaksiz, E.; Parlak, M.; Yilmaz, S.; Polat, I.; Altunbas, M.; Turksoy, M.; Topkaya, R.; Ozdogan, K. (ELSEVIER SCIENCE SA, 2011)
The effect of Mn-doping on the vacuum deposited CdS thin films has been investigated by studying the changes in the structural, optical and magnetic properties of the films. A thin Mn layer evaporated on the CdS film surface served as the source layer for the diffusion doping. Doping was accomplished by annealing the CdS/Mn stack layers at the temperature range from 300 degrees C to 400 degrees C in step of 50 degrees C for 30 min under vacuum. The X-ray diffraction results showed that the undoped CdS film had a zinc-blende structure with a strong preferred orientation along the (1 1 1)direction. The incorporation of Mn did not cause any change in the texture but reduced the peak intensity and lead to a smaller crystallite size. Investigation of surface morphology using atomic force microscopy confirmed the decrease in the grain size with the Mn diffusion. In addition, a more uniform grain size distribution was observed in the doped films. X-ray photoelectron spectroscopy analysis showed that Mn atoms on the surface of the films were bounded to either sulphur or oxygen atoms. Auger electron spectroscopy of the diffusion-doped CdS sample at 350 degrees C indicated that the atomic Mn concentration was higher close to the surface region and Mn was distributed with a steadily decreasing profile through the bulk of the film with an average atomic concentration value around few percent. Band gap energy of the undoped sample decreased from 2.42 to 2.36 eV upon Mn diffusion at 400 degrees C. The magnetization of films as a function of magnetic field and temperature were measured. Clear ferromagnetic loops were observed for the Mn diffusion-doped CdS films prepared by annealing above 350 degrees C. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Semiconductors; Thin films; Annealing; X-ray photo-emission spectroscopy (XPS); Mn-doped CdS; Ferromagnetism; CADMIUM-SULFIDE; SEMICONDUCTOR ZN1-XCRXTE; SPRAY-PYROLYSIS; GROWTH; Materials Science